2019
DOI: 10.1152/ajpheart.00564.2018
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of functional ryanodine receptors in rat mesenteric collecting lymphatic vessels

Abstract: In the current study, the potential contributions of ryanodine receptors (RyRs) to intrinsic pumping and responsiveness to substance P (SP) were investigated in isolated rat mesenteric collecting lymphatic vessels. Responses to SP were characterized in lymphatic vessels in the absence or presence of pretreatment with nifedipine to block L-type Ca2+ channels, caffeine to block normal release and uptake of Ca2+ from the sarcoplasmic reticulum, ryanodine to block all RyR isoforms, or dantrolene to more selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 77 publications
2
15
1
Order By: Relevance
“…In this regard, transcripts encoding all three RYR subtypes (RYR1, RYR2, and RYR3) have been detected in RNA isolated from human dermal and rat mesenteric LVs. In the latter preparation, the RYR2 and RYR3 proteins were revealed by whole-vessel mount immunostaining, but expression of the RYR1 subtype was not reported (Hasselhof et al, 2016;Jo et al, 2019). In this study, we provide initial direct evidence for the presence of RYR1 in freshly isolated populations of LMCs using a RYR1-specific antibody in flow cytometry.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this regard, transcripts encoding all three RYR subtypes (RYR1, RYR2, and RYR3) have been detected in RNA isolated from human dermal and rat mesenteric LVs. In the latter preparation, the RYR2 and RYR3 proteins were revealed by whole-vessel mount immunostaining, but expression of the RYR1 subtype was not reported (Hasselhof et al, 2016;Jo et al, 2019). In this study, we provide initial direct evidence for the presence of RYR1 in freshly isolated populations of LMCs using a RYR1-specific antibody in flow cytometry.…”
Section: Discussionmentioning
confidence: 78%
“…Currently, DANT is available in intravenous and oral formulations (Ratto and Joyner, 2020), with a topical composition recently patented (Henry, 2014). However, DANT has not received attention as an anti-lymphedema therapeutic, largely because the contribution of RYRs to lymph muscle contraction is regarded as minimal and the identity of the RYR subtypes (RYR1, RYR2, and RYR3) expressed by LMCs is unresolved (Atchison and Johnston, 1997;Atchison et al, 1998;Zhao and van Helden, 2003;Jo et al, 2019;Stolarz et al, 2019). Accordingly, the present study also determined whether the RYR1 protein, the therapeutic target for DANT, is expressed by freshly isolated LMCs.…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, while L-type calcium channel is partially responsible for differential contractile activity of mouse lymphatic vessels from various regions of the body, it controls both frequency and strength of phasic contractions in lymphatic vessel 15,60 . In the presence of ryanodine that inhibits ryanodine receptor, lymphatic vessels showed a decrease in contractile frequency and amplitude, without a change in tonic contraction 61 , suggesting critical roles of endoplasmic reticulum stored calcium in phasic contraction. Our data show that inhibition of SERCA by thapsigargin in lymphatic vessels diminished both phasic contractile frequency and amplitude without affecting the tone.…”
Section: Discussionmentioning
confidence: 98%
“…However, both cardiac and some smooth muscle cells display spontaneous depolarizations, which trigger voltage-dependent Ca 21 influx through dihydropyridine-sensitive Ca v 1.2 channels to fuel rhythmic contractions, a feature also shared by lymphatic muscle cells (Atchison and Johnston, 1997;Gashev, 2002;Zawieja, 2009;Lee et al, 2014). Notably, a recent study showed amplification of transcripts encoding all three RYR isoforms from rat mesenteric collecting lymph vessels, and detected RYR2 and RYR3 proteins in the muscle layer of these vessels; studies to detect the RYR1 protein apparently were not performed (Jo et al, 2019). Interestingly, RNAseq data obtained from human dermal lymphatics also detected all three RYR isoform genes (Hasselhof et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of DOX on RYRs and Ca 21 signaling in lymphatic muscle cells has yet to be established. Indeed, under basal conditions, the RYRs are not regarded as contributing significantly to rhythmic contractions in isolated lymph vessels (Atchison et al, 1998;Zhao and van Helden, 2003), and the molecular identity of the functional RYRs in lymphatic muscle cells is unknown (Muthuchamy et al, 2003), although isoforms RYR2 and RYR3 recently were detected in the smooth muscle layer of rat mesenteric collecting lymph vessels (Jo et al, 2019). Regardless, we considered whether the pharmacological activation of otherwise quiescent RYRs by DOX may explain its disruption of lymphatic rhythmic contractions.…”
Section: Doxorubicin Inhibits Lymphatic Contractions and Lymph Flowmentioning
confidence: 99%